2022
DOI: 10.20463/pan.2022.0009
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization and development of a questionnaire to determine physical activity barriers

Abstract: [Purpose] Considering the role of physical activity on public health and the high prevalence of physical inactivity worldwide, determining physical activity barriers is critical and will be a road map for future planning. This study aimed to develop a comprehensive questionnaire to determine physical activity barriers.[Methods] By reviewing previous studies, the main domains of the questionnaire were established. A physical activity expert interviewed 20 individuals aged 18 to 65 years. The results were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…They found that physical barriers such as pain and physical discomfort, psychological barriers such as a lack of self-discipline and motivation, and socio-ecological barriers such as a lack of time were reported to be major impediments to exercise participation. That is, it is very important to suggest an exercise method that can improve exercise compliance and effectively improve body composition and health while considering the barriers to exercise participation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…They found that physical barriers such as pain and physical discomfort, psychological barriers such as a lack of self-discipline and motivation, and socio-ecological barriers such as a lack of time were reported to be major impediments to exercise participation. That is, it is very important to suggest an exercise method that can improve exercise compliance and effectively improve body composition and health while considering the barriers to exercise participation [16,17].…”
Section: Introductionmentioning
confidence: 99%